Analisis Pengaruh Pendapatan Daerah dan Belanja Daerah Terhadap Pertumbuhan Ekonomi di Kabupaten Tapanuli Selatan (2011-2022) - Siregar, Ine Febrianti; Batubara, Rifka Fauziah; Hutapea, Ruth Septaria; Rahmawati, Sinta (Asosiasi Dosen Akuntansi Indonesia, 2023)
The study aimed at evaluating the impact of regional income and regional expenditure on economic growth in South Tapanuli Regency over a 12 year period, namely from 2011 to 2022. The approach applied in this study uses multiple linear regression analysis techniques using time series data collected by Central Statistics Agency (BPS). This study shows that both regional income and regional expenditure simultaneously have a large impact on economic growth. In the T Test (Partial), the probability of regional income is 0.000 < 5% or 0.05, so H0 is not approved and Ha is approved. Likewise, the probability of regional spending is 0.0206 < 5% or 0.05, so it can indicate where H0 is approved and Ha is approved (which is at the 5% or 0.05 significance level). The F (Simultaneous) test produces a Prob (F-statistic) value of 0.0000003 < 5% or 0.05, so H0 is not approved and Ha is approved. These findings can be a basis for developing policies and strategies for sustainable and quality economic development in South Tapanuli Regency.